Integration of a brief, transdiagnostic psychological intervention in the care of adolescents and young adults with HIV in Kenya: Protocol for a cluster randomized clinical trial. - Cyrus Mugo; Irene Njuguna; Vincent Maganga; Brian P Flaherty; Anjuli D Wagner; Ferdinand C Mukumbang; Shannon Dorsey; Daniel Mwai; Caren Mburu; Manasi Kumar; Anne Mbwayo; Muthoni Mathai; et al. (PLoS ONE)
Adolescents and young adults with HIV (AYH) are at greater risk for mental health conditions. Provision of mental health services to AYH is limited by an overburdened and untrained workforce, and psychological interventions ill-adapted for adolescent HIV care. Brief, transdiagnostic psychological interventions delivered in the HIV clinics may address some of these challenges. We will evaluate the PRO-ACT intervention in a hybrid type 1 cluster randomized clinical trial (NCT06247527) in 30 HIV clinics in 3 counties in Kenya. PRO-ACT is a cognitive behavioral therapy with 5 modules: Psychoeducation, Relaxation, prOblem-solving, behavioral Activation and Cognitive coping, delivered to AYH by trained health providers without specialist mental health training in 4-6 sessions within 6 months. We performed stratified randomization with matching to balance for county and facility size to assign 5 intervention (PRO-ACT) and 5 control (standard of care) clinics in each of the 3 counties. Screening of AYH ages 16-24 years will be conducted using the 9-item patient health questionnaire (PHQ-9). Up to 300 AYH with psychological distress (PHQ-9 score>4) will be enrolled in each arm. Further assessments will include the 5-item ASK suicide screening questions (ASQ), 7-item Generalized Anxiety Disorder (GAD-7), 20-item Child and Adolescent Trauma Screen (CATS)/PTSD Checklist for DSM-5 (PCL-5), self-reported treatment adherence, and HIV viral loads. Follow-up assessments will be conducted at month 3, 6, 9 and 12. Mixed methods will be used to measure implementation outcomes, cost-effectiveness, and characterize determinants of implementation. Primary analysis of PRO-ACT effectiveness will be conducted at month 6 (near term treatment effect), and month 12 (treatment effect sustainability) comparing PHQ-9 mean scores between treatment and control groups. Secondary analyses will compare GAD-7, CATS/PCL-5, adherence and viral suppression between the groups. The study will inform integration efforts of holistic mental health services in HIV care.